TINGKAT LITERASI KEBENCANAAN PADA SISWA SEKOLAH MENENGAH PERTAMA DI KOTA TANGERANG: SEBUAH STUDI PENDAHULUAN DALAM MEMBANGUN RESILIENSI SEKOLAH MELALUI MITIGASI BENCANA - Rahmat, Hayatul Khairul; Wahyuningtyas, Ayu (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Tangerang City is one of seven cities in Indonesia that is recorded as a disaster risk reduction center. According to InaRISK data, Tangerang City experiences several natural disaster vulnerabilities, including landslides, urban flooding, earthquakes, and droughts. Considering the potential hazards, serious action is needed from various parties to reduce these hazards and increase disaster awareness in the community, especially in the school community. Schools have an important role to provide provisions for their students through disaster education so that they can face every potential disaster. One way to increase disaster literacy in general is to provide provisions for students at school. This study aims to identify: (a) the level of disaster literacy among students of SMP Negeri 32 Tangerang City; and (b) school efforts in building school resilience through disaster mitigation. A mixed method with a sequential explanatory strategy was used as the method in this study. The findings of this study are: (a) the level of disaster literacy among students of SMP Negeri 32 Tangerang City is in the good category, which is 81%; (b) School efforts in building school resilience through disaster mitigation are carried out through three activities, namely by integrating disaster risk reduction into subjects, through co-curricular activities, and through extra-curricular activities. Several of these activities are part of disaster risk reduction to build school resilience in facing various disasters at SMP Negeri 32 Kota Tangerang.